Imatinib-induced extensive hyperpigmentation in a case of chronic myeloid leukemia - Pradeep Balasubramanian; Soumya Jagadeesan; Jacob Thomas (Wolters Kluwer Medknow Publications, 2015)
Imatinib, a tyrosine kinase inhibitor, is well known to cause hypopigmentation because of its inhibitory effect on melanocytes. Herewith we report a case of chronic myeloid leukemia who developed extensive hyperpigmentation following imatinib therapy.